Editorial - Aguirre Chavez, Felipe (2020)
Throughout its history, humanity has faced various pandemics with a crucial impact on culture, the economy, human relationships, and family ties. The pandemic, like all aspects of life, presents both light and darkness. Its dark side brings pain and death, but on the other hand, it emerges the opportunity to rethink our lives, what we do, and how we should project ourselves as a country and as human beings.